The effect of feeding treated fish meal by different methods of heat sterilization on broiler performance - Ahmed, Mohamed Elamin; Idris, Abbaker Ali; Ahmed, Awatif Mudathir (Journal of Veterinary Medicine and Animal Production, 2021)
The present experiment was conducted to investigate the possibility of using local sun-dried fishmeal in broiler diets and examine the effect of different methods of heat sterilization on microorganisms content of fishmeal. Serial dilutions for pour-plate were used for counting the number of bacterial colonies. Chemical analysis revealed that D.M., C.P., E.E., C.F., ash, Ca, P, Mg, lysine and methionine of sun-dried fishmeal were 96.13, 35.0, 10.84, 0.0, 45.31, 8.0, 2.22, 0.51, 4.82 and 1.52%, respectively. Four experimental diets were formulated to meet NRC (1994) recommendations. The sundried fishmeal (A) was sterilized by autoclaving at 121°C for 20 minutes to give type B fishmeal, oven heating at 80°C for 25 minutes to give type C fishmeal and oven heating at 75°C for 25 minutes to give type D fishmeal. Diet A is a control containing 5% super-concentrate; Diet B, C and D were contained 10% sterilized fishmeal. The experimental diets were fed to 160 unsexed one-day old broiler chicks (Hybro). Body weight gain, feed intake, feed conversion ratio and protein efficiency ratio were recorded weekly. Evaluation for bacterial count and isolation of salmonella for the different diets were investigated. At dilution 10 -1, 10-2, 10-3 and 10-4 autoclaving at 121 °C for 20 minutes was more effective in reducing number of bacterial colonies compared to the other heat treatments which revealed no significant (P≥0.05) differences. Body weight gain, FCR and PER were negatively (P≤0.01) influenced by the dietary treatments. Birds fed the control diet showed better performance than those subjected to any of the fishmeal under test. The experimental diets did not significantly (P≥0.05) affect dressing out percentage and sensory attributes. In conclusion the results of the current study indicated that fishmeal caused a significant depression in feed intake, body weight gain and feed efficiency. Autoclaving at 121°C for 20 minutes had significantly (P≤0.05) reduced number of colonies compared to the other heat treatments